Photophysical Properties of Chlorotriethylphosphinegold(I) - Kang, Jun-Gill; Jeong, Yong-Kwang; Oh, Sung-Il; Kim, Hyun-Jun; Park, C.; Tiekink, E.R.R. (Korean Chemical Soc, 2010)
Spectroscopic and quantum mechanical studies of the Et(3)PAuCl complex were performed to characterize the effect of aurophilicity on the optical properties. When excited with UV light at low temperature, the crystalline complex produced a deep luminescence in both the blue (high-energy) and red (low-energy) regions of the spectrum. The intensity of the low-energy luminescence was markedly reduced in the powdered state and quenched in the solution state. Time-dependent density functional theory (TD-DFT) calculations on electronic structures of both the ground and excited states of aggregates [Et(3)PAuCl](n) (n = 1 - 3) indicated that the low-energy luminescence was attributable to Au-centered transitions, which are significantly affected by aurophilic interactions. By contrast, the high-energy luminescence appeared to be independent of the state of the complex and was strongly associated with the charge transfer from Cl to Au.